Immunohistochemistry and Bioinformatics Identify GPX8 as a Potential Prognostic Biomarker and Target in Human Gastric Cancer - Zhang, Xiaojie; Xu, Heng; Zhang, Yunan; Sun, Chongyuan; Li, Zefeng; Hu, Chunfang; Zhao, Dongbing; Guo, Chunguang (Frontiers in Oncology, 2022)
Background Glutathione peroxidase 8 (GPX8) is a type II transmembrane protein with rare structural features belonging to the glutathione peroxidase family. The function of GPX8 in stomach adenocarcinoma has not been discovered clearly. Methods In this study, we comprehensively analyzed the expression of GPX8 in stomach adenocarcinoma and discovered that it is a potential target in the treatment of stomach adenocarcinoma. The immunohistochemical staining of GPX8 and survival analysis were performed in carcinoma tissue and adjacent tissues of 83 gastric cancer patients. The Gene Expression Profiling Interactive Analysis (GEPIA) database and Kaplan–Meier plotter database were used to evaluate the prognostic survival of GPX8 in stomach adenocarcinoma. The Cancer Genome Atlas (TCGA) database was used to download the microarray mRNA data of GPX8 and clinical information for cancer patients. The TIMER database and GSEA database were used to systematically evaluate the association of GPX8 and tumor-infiltrating lymphocytes in adenocarcinoma carcinoma. The STRING database was used to analyze protein-to-protein interactions of GPX8. The ROC curve was used to analyze the diagnostic effect of GPX8 in distinguishing outcomes between different subgroups, and a nomogram was constructed based on GPX8. Top transcription factor binding sites were analyzed using the QIAGEN database in the GPX8 gene promoter, and the functional enrichment analysis of GPX8 was done by GO and KEGG pathway enrichment analyses. Result Based on the GEPIA and TCGA databases, the mRNA expression of GPX8 was significantly higher in stomach adenocarcinoma compared with the adjacent normal tissues. The GEPIA and Kaplan–Meier plotter databases showed that a higher GPX8 expression level was correlated with poor prognosis of stomach adenocarcinoma, suggesting that GPX8 was a risk factor of poor prognosis in stomach adenocarcinoma. The TIMER database showed that the GPX8 expression level was positively correlated with infiltrating levels of CD8+ T cells, CD4+ T cells, macrophages, neutrophils, and dendritic cells in stomach adenocarcinoma. The GSEA database indicated that GPX8 was positively correlated with B cells, dendritic cells, CD4+ T cells, CD8+ T cells, macrophages, mast cells, monocytes, and natural killer cells. At last, GO analysis indicated that the biological processes were enriched in collagen fibril organization, endodermal cell differentiation, collagen metabolic process, extracellular matrix organization, etc. KEGG signaling pathway analysis showed that GPX8 was correlated with protein digestion and absorption, extracellular matrix receptor interaction, AGE/RAGE signaling pathway, etc. The GSEA database showed that GPX8 was positively associated with angiogenesis, epithelial mesenchymal transition, hedgehog signaling, etc. The immunohistochemical staining of GPX8 and survival analysis in 83 gastric cancer patients showed that the OS rate of patients with a high GPX8 expression was significantly lower than that of the low GPX8 expression group. Conclusion GPX8 is an important factor which might be a potential target in the treatment of stomach adenocarcinoma.